In Vivo Assembly of Artificial Metalloenzymes and Application in Whole‐Cell Biocatalysis. (1st February 2021) - Chordia, Shreyans; Narasimhan, Siddarth; Lucini Paioni, Alessandra; Baldus, Marc; Roelfes, Gerard
Abstract: We report the supramolecular assembly of artificial metalloenzymes (ArMs), based on the Lactococcal multidrug resistance regulator (LmrR) and an exogeneous copper(II)–phenanthroline complex, in the cytoplasm of E. coli cells. A combination of catalysis, cell‐fractionation, and inhibitor experiments, supplemented with in‐cell solid‐state NMR spectroscopy, confirmed the in‐cell assembly. The ArM‐containing whole cells were active in the catalysis of the enantioselective Friedel–Crafts alkylation of indoles and the Diels–Alder reaction of azachalcone with cyclopentadiene. Directed evolution resulted in two different improved mutants for both reactions, LmrR_A92E_M8D and LmrR_A92E_V15A, respectively. The whole‐cell ArM system required no engineering of the microbial host, the protein scaffold, or the cofactor to achieve ArM assembly and catalysis. We consider this a key step towards integrating abiological catalysis with biosynthesis to generate a hybrid metabolism. Abstract : Artificial metalloenzymes were created by supramolecular assembly in the cytoplasm of E. coli cells. The cells were then applied to the enantioselective biocatalysis of a Friedel–Crafts alkylation of indoles (see picture) and a Diels–Alder reaction. Directed evolution of the artificial metalloenzymes inside the cells provided improved variants for both whole‐cell biocatalytic reactions.